1998
DOI: 10.1038/sj.bdj.4809551
|View full text |Cite
|
Sign up to set email alerts
|

The emotional effects of tooth loss in edentulous people

Abstract: Tooth loss can be disabling and handicapping. It has a profound impact on the lives of some people, even those who are apparently coping well with dentures. The profession needs to consider how it can prepare people for the effects of tooth loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
217
0
22

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(247 citation statements)
references
References 0 publications
8
217
0
22
Order By: Relevance
“…A qualitative methodology is adopted to allow identification of the full range of impacts identified by participants. Such an approach has been used previously in dental settings to examine a range of topics, including the emotional effects of tooth loss, 13 the impact of loss of part of the face 14 and the stress in dental practice. 15 …”
Section: Research Behavioural Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative methodology is adopted to allow identification of the full range of impacts identified by participants. Such an approach has been used previously in dental settings to examine a range of topics, including the emotional effects of tooth loss, 13 the impact of loss of part of the face 14 and the stress in dental practice. 15 …”
Section: Research Behavioural Dentistrymentioning
confidence: 99%
“…Similar findings have been reported for individuals with facial disfigurement and for individuals who experience tooth loss. 13,35 Established personal relationships can also be strained. People recounted becoming irritable or agitated around dental appointments and perceived partners to lack understanding or tolerance of their anxiety.…”
Section: Social Impactmentioning
confidence: 99%
“…A qualitative study into the emotional effects of total tooth loss revealed a wide range of reactions. 11 The main themes identified in relation to tooth loss were: bereavement; loss of self confidence; concerns about appearance and self image; tooth loss as a taboo subject which could not be discussed with other people; keeping tooth loss secret; the need for prosthodontic privacy; behaviour change; premature ageing; and a lack of…”
mentioning
confidence: 99%
“…22 Así también se obtuvo que el 20,4 % usa prótesis ya sea total o parcial, en el cual la mayoría de los pacientes les gustaría cambiar el aspecto de su prótesis, ya sea por el tamaño de los dientes, color de encía o de dientes. Fiske et al han demostrado que pacientes portadores de prótesis han disminuido su confianza y una alteración en la socialización y en la forma de relacionarse, 23 además según Emani en el 2013, menciona que los pacientes portadores de prótesis presentan limitaciones funcionales. 24 Pascual en el año 2006, manifiesta que de acuerdo a su investigación, el color de los dientes en una prótesis es un factor importante en la sonrisa.…”
Section: Discussionunclassified